Regression Analysis by Example - Samprit Chatterjee 1938-; Ali S. Hadi; Bertram Price 1939- (USA John Wiley & Sons, 2000)
"Suitable for anyone with an understanding of elementary statistics, Regression Analysis by Example, Third Edition illustrates methods of regression analysis, with examples containing the types of irregularities commonly encountered in the real world. Each example isolates one or two techniques and features detailed discussions of the techniques themselves, the required assumptions, and the evaluated success of each technique. Each of the methods described can be carried out with most currently available statistical software packages."--Jacket
Preface -- Introduction -- Simple linear regression -- Multiple linear regression -- Regression diagnostics: detection of model violations -- Qualitative variables a predictors -- Transformation of variables -- Weighted least squares -- The problem of correlated errors -- Analysis of collinear data -- Biased estimation of regression coefficients -- Variable selection procedures -- Logistic regression
Keywords: Social Sciences (3GdYdhe GdGLJeGYjIs; Regression analysis; General